The Effect of Emotional Intelligence, and Social Support on Career Readiness with Self-Efficacy Career Readiness as Mediation Variables - Dwi Sesri Andini; Hendra Lukito (Almana : Jurnal Manajemen dan Bisnis, 2022)
The work readiness of final-year students shows the quality of available human resources. This research aims to determine the influence of career readiness on the dependent variables and the mediating relationship for the variables of emotional independence, social support, and career decision self-efficacy. Meanwhile, the mediating relationship between emotional intelligence and social support on career readiness through career decisions for undergraduate students at Andalas University. The method of collecting data in this study was by distributing questionnaires to 245 student respondents. The research approach used is correlation investigation to find the relationship between variables. The data collection method for the sample is probability sampling with a simple random sampling technique and using SmartPLS software. The data analysis process used is descriptive analysis and PLS analysis. PLS analysis using the Inner model, outer model, and hypothesis testing. This study has seven hypotheses. Four of them are supported, and three are not supported. The results of this study indicate a positive and significant relationship between social support on career decision self-efficacy and social support on career readiness. At the same time, there is also a mediating relationship between social support on career readiness through career readiness self-efficacy. However, there is no relationship between emotional intelligence variables on career readiness, career readiness, and mediation relationships.